(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2024)
Hemophilia is an X-linked monogenic disorder. Gene therapy holds the promise of a cure with a single intravenous administration of an adeno-associated viral vector engineered to express high level and, in some cases, hyperactive coagulation factors. Here we present a summary of active gene therapy clinical trials for haemophilia B. It has been demonstrated the potential to obtain Factor IX activity in normal range and otherwise expression up to ten years. It is relevant to control the immune response to produce suitable factor IX levels.